YOUNG SOCIAL ENTREPRENEURSHIP IN SAUDI ARABIA - Rafif Rajkhan, Nabil Tarifi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Young social entrepreneurs are individuals who approach a social problem with entrepreneurial spirit and business. Social entrepreneurship is a genuine combination of the entrepreneurial and caring professions. Meanwhile, business entrepreneurs make businesses, social entrepreneurs make change. Other caring professionals following more traditional paths to do their work and operate within existing structures to help others. The study aimed to investigate the factor that allowed young social entrepreneurs to pursue independent livelihoods and increase in self-esteem in Saudi Arabia. The sample population for this study consist of youth entrepreneurship aged between 15 years and 24 years. The survey was prepared to collect primary and secondary data about young social entrepreneurship. The design used in this study is an online survey which responded by 50 respondents to give their opinions about young social entrepreneurship in Saudi Arabia. The survey questions helped to identify the public opinion about young social entrepreneurship and their perceptions towards of effective participation of those young social entrepreneurs.